The use of fish silage to increase feed efficiency and growth of grouper (Epinephelus coioides) in floating net cages - Agus Putra AS; Muhammad Amin; Baihaqi Baihaqi; Muhammad Hatta; Eva Ayuzar (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
This study aimed to investigate the efficiency of fish silage mixed in compounded diets on growth and survival rate of grouper (Epinephelus coioides). Grouper (2,340,24 cm, and 4,171,82 g) were divided into four groups and cultivated in 1x1x1,5 m floating net cages. Each group fed with compounded diets containing 0, 1, 3 and 5 g/kg fish silage diet twice daily. Fish were sampled for growth performances and feed efficiency at 14 days interval for 10 weeks. Results indicated that compounded diets at 1 and 3 g/kg silage affected the growth rate. Total length, specific growth rate and weight gain significantly increased in fish received 1 and 3 g/kg silage diets. The feed intake seen to be highest in groups administered 3 g/kg silage, whereas the best feed conversion ratio was found in fish fed 1 g/kg silage. Thus, this study indicated that using fish silage in compounded diets may affect feed efficiency and growth performances of grouper juveniles.Keywords:Artificial dietFeedingFish silageGrouperNet cages